Epidemiological analysis of death among patients on maintenance hemodialysis: results from the beijing blood purification quality Control and Improvement Center - Jing Liu; Huixian Zhang; Zongli Diao; Wang Guo; Hongdong Huang; Li Zuo; Wenhu Liu (BMC Nephrology, 2023)
Abstract Background China has the largest number of patients on maintenance hemodialysis (MHD) worldwide. Despite continuous improvements in hemodialysis techniques, patients on MHD have a higher mortality rate than the general population. Understanding the characteristics of death in this population can better promote clinical practice, thereby improving patients’ survival. Methods We collected demographic and clinical data for patients on MHD registered in the Beijing Blood Purification Quality Control and Improvement Center database from 2014 to 2020. The annual mortality rate was calculatedand the primary cause of end-stage renal disease (ESRD), dialysis vintage, and cause of death among deceased patients were analyzed. Results (1) 24,363 patients on MHD were included, of which 6,065 patients died from 2014 to 2020. The annual mortality rate fluctuated between 7.4% and 8.0%. The median age of death was 70.0 (60.8–79.0) years and the male to female ratio was 1.27:1 (2). The top three primary causes of ESRD in deceased patients were chronic glomerulonephritis (CGN), diabetic nephropathy (DN), and hypertensive nephropathy (HN). Comparison of the annual mortality rate showed DN > HN > CGN (3). The median dialysis vintage of deceased patients was 3.7 (1.8–6.9) years, which slowly increased annually. Patients with diabetes had a shorter dialysis vintage than patients without diabetes (3.4 vs. 4.1 years, Z = 8.3, P < 0.001) (4). The major causes of death were cardiovascular disease (20.2%), sudden death (18.1%), infection (17.9%), and cerebrovascular disease (12.6%). Proportions of death from cardiovascular disease, infection, and sudden death were higher in patients with diabetes (22.2%, 20.2%, and 20.0%) than patients without diabetes (18.4%, 15.8%, and 16.3%). Sudden death was the leading cause of death in young (18–44 years; 27.0%) and middle aged (45–64 years; 20.8%) patients, whereas infection was the leading cause of death in patients aged ≥ 75 years (24.5%). Conclusion The annual mortality rate of patients on MHD in Beijing was relatively stable from 2014 to 2020. Sudden death was more likely to occur in young and middle-aged patients, and more patients aged ≥ 75 years died from infections.